2020
DOI: 10.1051/e3sconf/202017513028
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and its key factors: an alternative view on the factors stimulating agriculture growth

Abstract: This research study makes an attempt to study the impacts of natural resources as well as financial and labor factors on economic development of contemporary states. Also, it investigates the correlation between all these factors mentioned above, in the context of countries’ economic growth. The obtained here results have helped us determine the core reasons behind international migration as a global phenomenon applicable to all countries without exceptions. Indirectly, we also demonstrate the transforming rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Regmi and Weber (1996) concluded that realistic sustainable agricultural development for small farmers is still a fiction. In addition, Wajeetongratana (2020) observed the favorable effect of a number of industrial characteristics on domestic and worldwide markets. The previous studies have focused on the relationship between government spending and economic expansion, labor migration, poverty, and agriculture growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regmi and Weber (1996) concluded that realistic sustainable agricultural development for small farmers is still a fiction. In addition, Wajeetongratana (2020) observed the favorable effect of a number of industrial characteristics on domestic and worldwide markets. The previous studies have focused on the relationship between government spending and economic expansion, labor migration, poverty, and agriculture growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In academic researches, the realization of various correlated factors of economic growth and its dynamic progress has always been taken among the top priorities (Wajeetongratana, 2020;Curzio et al, 1994;Zahka, 1990). Analysis of economic growth, its stages, cycles, required resources for growth, and related policies underpin scholars to continuously engage in the system and investigate the central causes of it over a long period.…”
Section: Introductionmentioning
confidence: 99%